PENGETAHUAN DAN SIKAP PERAWAT TENTANG ORGANISASI PROFESI PPNI DI RS JASA KARTINI KOTA TASIKMALAYA - mardiana ramdhan (HealthCare Nursing Journal, 2019)
The background is many PPNI members did not known the role, function, and utilized PPNI organization, so that was not supported for professional organizations. PPNI was targeted for the condition of Indonesian nurses that not prosperous. And for PPNI was felt much hampered to activitied because it has not received the support of member. The purpose of this research was to description knowledge and attitude of nurses about professional organizations PPNI in jasa kartini hospital. This research used the descriptive method with large of sample until 70 respondent, and the instrument used questionnaire which has been tested validity and reliability. Analysis in the research used univariate analysis. The result knowledge of nurses less, sufficient, good is 38,6%, 38,6%, 22,9% respectively. The result attitude of nurses positive as 54,4%, and negative as 45,5%. This can be concluded with the nursing issues about professional organizations was corrected with evidenced by the results of research. Then it will be a material evaluation for the PPNI commissariats Jasa Kartini Hospital until PPNI officials in Tasikmalaya city to improve the work program, in improve knowledge and attitude of nurses, especially for nurses in Jasa kartini hospital, generaly for all nurses in Tasikmalaya City.